Mormons in Paris : polygamy on the French stage, 1874-1892 - Cropper, Corry; Cropper, Corry; Flood, Christopher M., 1975-; Flood, Christopher M., 1975-; Leroy, Louis, 1812-1885; Mars, Antony, 1862-1915; Bernède, Arthur, 1871-1937; Chivot, Henri, 1830-1897 (Scènes francophones., 2021)
"In the late nineteenth century, numerous French plays, novels, cartoons, and works of art focused on Mormons. Unlike American authors who portrayed Mormons as malevolent "others," however, French dramatists used Mormonism to point out hypocrisy in their own culture. Aren't Mormon women, because of their numbers in a household, more liberated than French women who can't divorce? What is polygamy but another name for multiple mistresses? This new critical edition presents translations of four musical comedies staged or published in France in the late 1800s: Mormons in Paris (1874), Berthelier Meets the Mormons (1875), Japheth's Twelve Wives (1890), and Stephana's Jewel (1892). Each is accompanied by a short contextualizing introduction with details about the music, playwrights, and staging. Humorous and largely unknown, these plays use Mormonism to explore and mock changing French mentalities during the Third Republic, lampooning shifting attitudes and evolving laws about marriage, divorce, and gender roles"--